2018
DOI: 10.1177/1055665618775730
|View full text |Cite
|
Sign up to set email alerts
|

Tessier Number 30 Median Mandibular Cleft With Congenital Heart Anomalies in Qena, Egypt

Abstract: Median cleft deformities of the lower lip and mandible are very rare congenital anomalies. Our patient had median cleft of the lower lip, mandible, and the chin with tongue duplication, ankyloglossia, and cleft strap muscles with 2 neck contracture bands. This anomaly was associated with congenital heart disease transposition of great vessels, large ventricular septal defect, and severe pulmonary stenosis. Early repair was done at 6 months to improve feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…We found that the lack of miRNAs in mice led to a cleft lip‐like phenotype in the mandible. A similar symptom in humans, midline cleft of the lower lip, is known to be a rare congenital disease, which has been identified as Tessier 30 (Ali, 2019; Ladani et al, 2013; Oostrom et al, 1996). It is possible that changes in the expression of miRNAs cause the midline cleft of the lower lip in the human patient.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the lack of miRNAs in mice led to a cleft lip‐like phenotype in the mandible. A similar symptom in humans, midline cleft of the lower lip, is known to be a rare congenital disease, which has been identified as Tessier 30 (Ali, 2019; Ladani et al, 2013; Oostrom et al, 1996). It is possible that changes in the expression of miRNAs cause the midline cleft of the lower lip in the human patient.…”
Section: Resultsmentioning
confidence: 99%
“…Dans les formes sévères, l'épiglotte ou l´os hyoïde peuvent être absente et le cartilage thyroïdien peut être sous-développé [ 3 ]. Parfois, il peut y avoir un cordon cervical médian [ 11 ] comme dans notre cas. Les muscles hyoïdiens peuvent être atrophiques et représentés par un tissu fibreux provoquant un bombement du cou au cours de l'effort [ 10 ].…”
Section: Discussionunclassified
“…En 2001 Seyhan et al . [ 12 ] ont rapporté un cas de fente sternale associé à une cardiopathie, aussi en 2018 Ahmed Ali [ 11 ] a rapporté un cas de fente mandibulaire associé à une malformation cardiaque. À la lumière de ces données un bilan complet à la recherche d'autres malformations congénitales associées chez notre patiente a été réalisé, revenu complètement normal.…”
Section: Discussionunclassified
“…It may be possible to support the soft tissue repair with resorbable fixation or a resorbable suture. A number of cases would seem to have made use of this in the repair of this cleft (Ladani et al, 2013; Rao et al, 2015; Scheckter et al, 2018; Walker et al, 2019a; Ali, 2019).…”
Section: Discussionmentioning
confidence: 99%